Nationwide study of basic and instrumental activities of daily living in individuals aged 65+ living at home - Yıldız, Nadire Gülçin; Aydın, Halide Zeynep; Aydın, Kemal (Nevzat Demirci, 2023)
The limitations encountered by aging individuals 65+ in Turkey in their basic and instrumental activities of daily living were examined according to gender and age i.e., specifically for 65-74 and 75+ age groups. Microdata from the Turkey Health Survey implemented by the Turkish Statistical Institute (TurkStat) in 2019 were used in the analyses. According to the findings of this country-wide research, the results indicated that of the 2457 people aged 65+ living in their own homes, 11.2% were limited in activities of daily living (ADL), and 45.8% were limited in their instrumental activities of daily living (IADL). The ADL and IADL limitations also increased significantly according to age and gender. The prevalence of ADL limitations across Turkey was 4.5%, 1.9% in men aged 65-74, and 7.2% in women aged 65-74. In elderly individuals aged 75+, the prevalence of ADL limitations was found to be 13.7% in men and 21.7% in women. Based on the results of the Instrumental Activities of Daily Living module (IADL) results, 46.9% of men between the ages of 65-74 were limited in IADL, while this rate was found to be 72% for women. In both activities, the prevalence of limitations in women was more than twice as high as in men. The prevalence of ADL and IADL limitations differed significantly by gender and age groups (p<0.05).
Keywords: Activities of Daily Living; Age; Gender; Geriatrics; Mental Health; Public Health; Quality of Life